2012
DOI: 10.1038/jp.2012.138
|View full text |Cite
|
Sign up to set email alerts
|

Passive cooling during transport of asphyxiated term newborns

Abstract: Objective To evaluate the efficacy and safety of passive cooling during transport of asphyxiated newborns. Study Design Retrospective medical record review of newborns with perinatal asphyxia transported for hypothermia between July 2007 and June 2010. Results Forty-three newborns were transported, 27 of whom were passively cooled. Twenty (74%) passively cooled newborns arrived with axillary temperature between 32.5 and 34.5 °C. One newborn (4%) arrived with a subtherapeutic temperature, and 6 (22%) had te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 30 publications
2
36
1
2
Order By: Relevance
“…Overall, just under two-thirds of infants with HIE retrieved by the Wellington NeTS received timely initiation of TH. This figure is comparable to previously published reports on the efficacy of manual cooling during neonatal transport, and it highlights the limitation of this strategy to provide timely neuroprotection for a significant proportion of outborn infants with HIE [11, 17, 24, 25]. …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Overall, just under two-thirds of infants with HIE retrieved by the Wellington NeTS received timely initiation of TH. This figure is comparable to previously published reports on the efficacy of manual cooling during neonatal transport, and it highlights the limitation of this strategy to provide timely neuroprotection for a significant proportion of outborn infants with HIE [11, 17, 24, 25]. …”
Section: Discussionsupporting
confidence: 77%
“…Passive cooling, by removing external heat sources, or active cooling using cool packs have been shown to effectively reduce infants’ core temperature [11-14]. Continuous rectal temperature monitoring and adherence to a strict cooling guideline are recommended for the safe administration of TH without a servo-controlled cooling device.…”
Section: Introductionmentioning
confidence: 99%
“…To date, induced hypothermia by either selective head or whole body cooling within 6 hours of birth 1-3 is the only effective treatment for HIE shown to decrease the combined outcome of death or severe neurodisability at 18 months. 4-10 Several randomized clinical trials 5,7,9 and other single-institution studies [11][12][13][14][15][16] have included protocols that have initiated and/or continued cooling therapy during interfacility transport of "outborn" neonates delivered far from a cooling center or referred several hours after delivery. Although these studies have shown that cooling on transport is feasible and provide guidelines for protocol development, 17 efficacy and safety concerns such as potential overcooling 13 remain in question.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing studies on this issue by NICDH reported a term late hypothermia that could be expected to provide insights as to whether the later timely application of therapeutic hypothermia is beneficial [9] . Cooling during transport could be an alternative approach as initiation of effective hypothermia is achieved significantly earlier, but clinical protocols and devices for cooling in transport are essential to ensure safety and efficacy [23,25] .…”
Section: Discussionmentioning
confidence: 99%